Dimethyl itaconate protects against lippolysacchride-induced mastitis in mice by activating MAPKs and Nrf2 and inhibiting NF-κB signaling pathways. (August 2019) - Zhao, Caijun; Jiang, Peng; He, Zhaoqi; Yuan, Xin; Guo, Jian; Li, Yanyi; Hu, Xiaoyu; Cao, Yongguo; Fu, Yunhe; Zhang, Naisheng
Abstract: Mastitis, as the main disease to affect the dry dairy cow with the characterized by increasing number of somatic cells in milk and reducing milk production, has been known as one of the most serious expensive disease for the dairy industry. Escherichia coli ( E.coli ), a gram negative bacterial, have normally been considered to be an opportunistic pathogen that can invade the mammary gland sometimes to cause inflammatory diseases. Lippolysacchride (LPS), as the co-cell wall component of the Escherichia coli ( E.coli ), is the main virulence factors to induce acute inflammation. Itaconate is an endogenous metabolite which has recently been reported to regulate the macrophage function and has the ability to reduce the secretion of pro-inflammatory cytokines, such as IL-6 and IL-12. Here, the aim of this study is to investigate the protective role of dimethyl itaconate (DI)-the membranepermeable derivative of itaconate, on LPS-induced mastitis in mice. To establish the model of mastitis, mice 5–7 day after delivery were utilized by nipple duct injection of LPS, while DI was treated 24h intraperitoneally before LPS injection. Further, the hematoxylin-eosin (H&E) staining was used to evaluate the pathological changes of the mammary gland, the inflammatory cytokines of TNF-α and IL-1β and the myeloperoxidase (MPO) activity were also measured respectively by enzyme-linked immunosorbent assay (ELISA) and MPO assay kit. To clarify the underling mechanisms of the protective role of DI on mastitis, the MAPKs, NF-κB and Nrf2 signaling pathways were detected via western blotting. The results demonstrated that DI markedly decreased the pathological injury of mammary, and considerably reduced the production of TNF-α and IL-1β, as well as up-regulated the Nrf2, HO-1, phosphorylation of p38 and ERK, but down-regulated TLR4 and phosphorylation of p65 NF-κB. Our research recommended that DI ameliorated LPS-induced mastitis which highlights itaconate may as a potential candidate to protect against mastitis. Graphical abstract: Image 1 Highlights: DI has protective effects against LPS-induced mastitis in mice. DI significantly decreases the secretion of TNF-α and IL-1β. DI inhibits LPS-induced TLR4 expression and NF-κB activation. DI up-regulated the MAPKs and Nrf2 actiation.